(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
This paper studies the main innovations introduced into the Mexican politicalelectoral system by three reforms between the 1940s and 1970s, during the administrations of Manuel Ávila Camacho (1940-1946), Adolfo López Mateos (1958-1964) and José López Portillo. (1976-1982). Our hypothesis proposes that, unlike other electoral reforms in the period from the promulgation of the 1917 Constitution to the 1977 reform, these three moments of reform led to unprecedented constitutional changes, in which the opposition, even without a significant presence and through various means, managed to introduce some of their proposals into the Chamber of Deputies. These three reforms were also influenced, to a greater or lesser degree, by the character of the six-year term in which they were developed, which helps to explain some of their characteristics.